Factors affecting women’s participation in career: a systematic review - Chen, Rose Siew Kee; Wan Othman, Wan Norhayati; Zainudin, Zaida Nor; Mohamad Yusop, Yusni (Human Resource Management Academic Research Society, 2020)
The objective of this study is to understand factors affecting women’s participation in career and ways to encourage women’s participation in career. Issue of women’s participation in career has been hotly discussed around the world. Results from different journal sources conducted in different countries were assimilated to attain better understanding of the factors affecting women’s participation in career and ways to encourage women’s participant in career. The core of this work builds on highlighting the main findings related to the factors affecting women’s participation in career and ways to encourage women’s participant in career in Malaysia, United States, Africa and India. The role of counsellor in the counselling session to help the women in their career participation and development has been discussed. The limitation of this review is the selected studies were only limited to Malaysia, United States, Africa, Canada and India.